Integration of Pancasila Values in Student Books of Islamic Religious Education and Character at High School Level - Achadi, M. Wasith; Noor Laila Fithriyana (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
Islamic Education and Character Education as a compulsory subject in high schools, has an important role in providing education and understanding related to Pancasila and religion, to prevent the influence of anti-Pancasila in Indonesia. The purpose of this study is to describe the integration of Pancasila values contained in the textbooks of Islamic Education and Character Education for senior high school students. This research is a library research. The results showed that some materials could be integrated with Pancasila values. (1) Class X, found in chapter I, chapter IV, VI, VII, VIII, and IX. Class XI, found in chapter I, III, IX, and XI. Class XII, found in chapter I, IV, V, VI, IX and X. (2) The integration of Pancasila values with these materials is expected to increase the spirit of nationalism and overcome the spread of anti-Pancasila ideology in Indonesia, especially among adolescents